Emergence Response of Telenomus podisi (Hymenoptera: Scelionidae) to Field Temperature Originated from Colonies Reared at Different Temperature Regimes - Colombo, Fernanda Caroline; Maciel, Rodrigo Mendes Antunes; Deniz, Matheus [UNESP]; Neves, Pedro Manuel Oliveira Janeiro; de Freitas Bueno, Adeney (Springer Nature, 2023)
We studied the impact of field temperature on the emergence of Telenomus podisi Ashmead (Hymenoptera: Scelionidae) after being released as either protected (encapsulated) or unprotected pupae close to adult emergence. Two independent bioassays (protected pupae vs. unprotected pupae) were carried out in a randomized block experimental design in a 2 (parasitoid rearing temperature regimes) ×4 (release positions within plant canopy) factorial scheme. One of the T. podisi colonies was reared at a constant temperature (25 °C) and 12:12 h L:D (Light: Dark) photoperiod. The second T. podisi colony was reared at fluctuating temperatures (20 °C during 12 h D and 30 °C during 12 h of L). Each bioassay had five replicates. Each replicate contained 40 pupae from each rearing temperature and release position within plant canopy. Parasitoid pupae were released in the bottom third, middle third, or upper third of the plant’s canopy, as well as between planting lines. Each bioassay was repeated six times (in different plant developmental stages: R1, R2, R3, R4, R5 and R6). There was no difference in emergence of parasitoids between colonies reared at different temperatures after exposure to field conditions. Emergence of T. podisi was reduced after pupae exposure to temperatures above 35 °C in the field, regardless of the rearing temperature. Telenomus podisi tolerates temperature fluctuations for emergence as long as they fit the optimal range (20 to 30 °C).
Keywords: Augmentative biological control; egg parasitoid; parasitoid release; T. podisi release